Cost, Controversy, Crisis: Low Back Pain and the Health of the Public - R. A. Deyo; D Cherkin; David C. Conrad; Ernest Volinn (1991)
In recent decades, there has been remarkable growth in scientific research examining the multiple ways in which racism can adversely affect health. This interest has been driven in part by the striking persistence of racial/ethnic inequities in health and ...Read More